Funcionalidad familiar y su interrelación con el consumo de drogas ilícitas en los adolescentes de Bachillerato de la Zona 7 del Ecuador. 2016. - Vega Elizalde, Miriam Margoth (2017)
The use of illicit drugs in adolescents is nowadays an important social phenomenon and a public health problem due to the individual, family and social harm that it generates. The present research aims to analyze the interrelationship between family functionality and illicit drug use in high school adolescents in zone 7 of Ecuador (Provinces of El Oro, Loja and Zamora) during the year 2016, the characterization of the family structure, and sociodemographic factors. A non-experimental, quantitative, descriptive and cross-sectional study has been made with a target population of 66,856 adolescents from educational institutions, at high school level zone 7, a stratified random sample of 960 adolescents between 15 and 19 years of age belonging to private educational establishments and fiscomisionales at high school level; who were given an survey, structured by general data; Test FFSIL; Socioeconomic status and consumption of illicit drugs. The data obtained were analyzed by the statistical test of Chi2, p value, Cramer's V and the OR with 95% CI. It was of drugs in schooling adolescents is 16, 30%. In the bivariate analysis it was observed that 21.80% of the adolescents living in dysfunctional families consume drugs, while 13.80% of the consumers live in functional families, a difference that is statistically significant (Chi2 of 9,790 and a value of P of 0.002), which shows that if there is an association between family functionality and illicit drug use. In conclusion, family dysfunctionality is related to illicit drug use in adolescents. There is greater consumption in those adolescents whose families are dysfunctional. Key words: Drugs, adolescents, family dynamics, family structure